AB0137 ROLE OF VIMENTIN AS A TARGET OF ANTIBODIES AGAINST CARBAMYLATED PROTEINS IN RHEUMATOID ARTHRITISPATIENTS. (June 2019) - Pecani, Arbi; Colasanti, Tania; Alessandri, Cristiano; Leopizzi, Martina; Mancini, Riccardo; Conti, Fabrizio; Valesini, Guido; Spinelli, Francesca Romana
Abstract : Background: Patients with Rheumatoid Arthritis (RA) have an increased risk of cardiovascular diseases (CVD). Inflammation and autoantibodies indipendently promote endothelial dysfunction, which is the earliest, reversible stage of atherosclerosis. In vitro studies have demonstrated that antibodies against carbamylated proteins (anti-CarP), recently described in RA patients, can induce the production of proatherosclerotic molecules like Vascular Cell Adhesion Molecule (VCAM-1) and activate Interleukin-1 Receptor-Associated Kinase (IRAK-1), Nuclear Factor kB (NF-kB), inducible Nitric Oxide Synthase (iNOS) in endothelial cells (1, 2). Moreover, anti-CarP are associated to endothelial dysfunction and subclinical atherosclerosis in RA patients (3). Objectives: Aims of the present study were: 1) to analyze the role of vimentin as a target of autoantibody response in the serum of patients with RA and 2) investigate the expression of vimentin and carbamylated proteins in endothelial cells. Methods: Consecutive RA patients were enrolled in this study. Vimentin was carbamylated and used as an antigen for the detection of anti-Vimentin Carbamylated antibodies (CarVim), through immunoenzymathic methods. Cells were incubated with anti-vimentin and carbamylated antibodies. The presence of vimentin and carbamylated proteins was investigated by immunofluorescence on the immortalized endothelial cell line EA.hy 926. Results: Eighty-eight (88) RA patients were enrolled in this study (F:M = 79:9, mean age = 56 ± 13 years). Anti-CarVim antibodies were present in 9% of the patients with a mean titre of di 442 aU/ML (IQR 303 aU/ml). Vimentin and carbamylated proteins were detected in the endothelial cells by immunofluorescence (Figure 1 ). Conclusion: The results of this study confirm that Vimentin is one of the antigenic targets of anti-CarP antibodies present in the serum of RA patients. The presence of carbamylated proteins and vimentin in endothelial cells suggests that anti-CarVim could bind the modified protein and determine endothelial activation and subsequent endothelial dysfunction. Reference: [1] Pecani A & Alessandri C et al, Arthr Res Ther 2016 [2] Pecani A et al, Reumatismo 2017 [3] Spinelli FR & Pecani A et al, BMC Musculoskelet Disord 2017. Disclosure of Interests: None declared